Does the impact of economic inequality on maternal and child health inequality exhibit a threshold effect? Evidence from China - Yao Yao; Yujie Cui; Wei Luan; Gordon Liu (Global Public Health)
When the economy (economic inequality) develops to a certain level, does the impact of economic inequality on health inequality change? Through threshold regression, this study analyses the impact of city-level economic inequality on the absolute and economic-related inequality in under-5 child mortality rate (U5MR) (2001–2012) and maternal mortality rate (MMR) (2001–2015), along with the threshold values for economic development stages and economic inequality. Findings show: For the relationship between economic inequality and absolute inequality in U5MR, as well as economic-related inequality, there exists an economic development threshold effect. For the relationship between economic inequality and absolute inequality in MMR, an economic inequality threshold effect is illustrated. The improvement of economic conditions contributes to alleviating inequality in U5MR. Economic development inequality has a significant impact on the equality of maternal health development, but for enhancing the equality of women's health, health promotion policies may be more feasible.